Role of Orthopantomogram in assessing the impacted third molar and its proximity to inferior alveolar nerve - S Saravana Kumar; A Pravindevaprasad; S Sundarapandian (Wolters Kluwer Medknow Publications, 2012)
Objective: The aim of this study was to determine the type of impacted teeth in a south Indian population with the use of orthopantomogram and to assess the risk of proximity of inferior alveolar nerve. Material and Methods: This is a retrospective study of 50 patients with asymptomatic Mandibular third molars screened and diagnosed at oral medicine . Panoramic radiographs were made for evaluation of identified cases. The angle of impacted Mandibular third molar was determined by the angle formed between the intersected longitudinal axes of the second and the third molars. Results: Of the 50 patients, mesioangular impaction (74%) was the most common and the proximity to the inferior alveolar nerve was more with the horizontal impactions Conclusion: Orthopantomogram is a simple two dimensional diagnostic procedure which can be adopted to assess the impaction before going for impaction to assess the anatomic proximity if inferior alveolar nerve (IAN) in relation to the third molar root so as to prevent the further complications.